Effect of Marble Powder Waste as Fine Aggregate Substitution in Rigid Pavement - Nukar, Maria Sesi; Sadillah, M.; Oktaviastuti, Blima (JURUSAN TEKNIK SIPIL, 2024)
The demand for construction materials, particularly for pavement construction, continues to rise, leading to a reduction in available material resources. To address this, an alternative approach has been developed by utilizing marble powder waste as a partial substitute for fine aggregate in rigid pavement construction. This study employs a quantitative, experimental research design aimed at determining the compressive and flexural strength of concrete when marble powder is used as a partial replacement. The compressive strength tests involved varying the marble powder content at 0%, 15%, 25%, and 35%, with assessments at both 7 and 28 days, targeting a planned concrete quality of fc' 21,7 MPa. The compressive strength values at 7 days for each variation are as follows: 0% (13,06 MPa), 15% (13,98 MPa), 25% (15,99 MPa), and 35% (14,10 MPa). At 28 days, the compressive strength results were 0% (22,00 MPa), 15% (23,79 MPa), 25% (16,97 MPa), and 35% (15,67 MPa). For the flexural strength tests, marble powder was substituted at levels of 0%, 15%, 25%, and 35% in concrete specimens measuring 12x50x120cm, with the load applied at 28 days. The maximum load recorded for each variation was 0% (4300 kg), 15% (3200 kg), 25% (4000 kg), and 35% (2500 kg). The average deflection observed was 0% (3,93mm), 15% (2,60mm), 25% (4,26mm), and 35% (2,37mm).